Memories of a teacher. On the 80th anniversary of George N. Carpun - Bobrov A.V.F.Ch.; Romanov M.S. (Hortus Botanicus, 2024)
The article contains the memories of the remarkable botanist, dendrologist and introductor – George N. Сarpun. The main areas of scientific interests of G. N. Carpun are described, as well as his views on various scientific problems, including the theory and practice of plant introduction on the Black Sea coast of the Caucasus, the origin and evolution of land plants, various philosophical questions are outlined.